Cocaine-Induced Asthma and the "Crack Lung": A Case Report - López-Félix, Victor A; González-Torres, Luis A; Gamboa-Meza, Alan; Alanís-Estrada, Gabriela; Moreno-Hoyos-Abril, Juan Francisco (Curēus (Palo Alto, CA), 2024)
Cocaine, the second most used illicit drug, is associated with cardiovascular, pulmonary, and other complications. Lung involvement associated with cocaine use, also known as "crack lung syndrome" (CLS), can elicit new-onset and exacerbate chronic pulmonary conditions. A 28-year-old female with a history of chronic controlled asthma arrived at the Emergency Department (ED), referring to cocaine inhalation, followed by symptoms compatible with an asthmatic crisis, requiring immediate steroid and bronchodilator therapy. Radiological studies and bronchoscopy confirmed CLS diagnosis. Despite treatment with oxygen, bronchodilators, and steroids, the asthmatic crises persisted. However, after 48 hours, we observed a complete regression of the lung infiltrates. This case highlights the importance of clinical suspicion, bronchoscopy findings, and the potential co-occurrence of CLS with asthma exacerbations. While computed tomography (CT) scans can be helpful, they should not be the only tool to diagnose CLS. The successful management of CLS involves the use of bronchodilators, steroids, and oxygen therapy and abstaining from cocaine use. Researchers should conduct further studies to diagnose and treat CLS in conjunction with acute asthma symptoms to assist this patient population better.